Deciphering the shifting role of intrinsic and extrinsic drivers on moss decomposition in peatlands over a 5‐year period. Issue 1 (3rd November 2021) - Shelley, Sarah J.; Brice, Deanne J.; Iversen, Colleen M.; Kolka, Randy K.; Sebestyen, Stephen D.; Griffiths, Natalie A.
Abstract : Bryophytes are largely responsible for globally significant carbon accumulation in peatland ecosystems. This accumulation is primarily caused by the slow decomposition of these mosses, which can be attributed to a combination of intrinsic (chemical) characteristics of decaying mosses and extrinsic (environmental) influences. Here we investigated the importance of intrinsic and extrinsic drivers of moss decomposition in peatlands and hypothesized that the early stages of decay will be driven primarily by intrinsic characteristics, while extrinsic drivers will become more important in the later phases of decomposition. We tested this hypothesis by placing litterbags of three moss types ( Sphagnum divinum, Sphagnum angustifolium/fallax and Polytrichum sp.) into hummock and hollow microtopographies in a bog and a lawn microtopography in a nearby poor fen in northern Minnesota, USA. Decomposition was measured over a 5‐year period and confirmed our hypothesis; while intrinsic and extrinsic variables were both important in driving decay rates over time, decay in the first year was primarily predicted by litter type, while extrinsic influences (e.g. peat temperature, moisture, nutrient limitation) that varied at peatland and microtopographic scales became more important by year 5. Though the nutrient (i.e. nitrogen [N] and phosphorus [P]) content of decaying mosses did not explain the variation in decay rates among litter types, analysis of N:P in moss litter suggested that litter‐decaying microorganisms became increasingly P‐limited over time. The majority of litter decomposition studies in peatlands are generally of short duration (< 3 years). Our study suggests that longer‐term studies are needed to reveal the roles of multiple drivers of moss decay. Improving the mechanistic understanding of decomposition processes in peatlands will be critical to developing more robust representations of peatlands and their ecosystem processes in carbon and climate models.